Estudo de transições de fase sob altas pressões para a perovskita [MHy]Mn(H2POO)3, hipofosfato de metil- hidrazina com manganês, via espectroscopia raman - LEITE, Fábio Furtado (2024)
Hybrid perovskites exhibiting a three-dimensional architecture (3D) ABX3, where A represents protonated amines or alkali metal cation, B represents divalent cation and X represents monoatomic (halide) or multiatomic (HCOO−, N− 3 , CN−, N(CN)− 2 , and H2PO− 2 ) anion, has been widely studied in recent years for its optoelectronic, nonlinear optical, dielectric1 and multiferroic properties . The perovskites with the formate group, single or double, are the most extensive and contain members with ferroelectric, multiferroic and photoluminescent properties2 4. It was observed that the hypophosphite ligand, H2POO−, has functional and structural properties similar to the formate anion, making it promising for the construction of new perovskites that exhibit a magnetic order. hypophosphites often have displacements and location outside the center of organic cations, that is, the potential for symmetry breaking is greater in hypophosphites than in formates. In chapter 1 of this work we carry out a bibliographical review about the family of organic metals ABX3. In chapter 2 we approach the theoretical foundations about the Raman spectroscopy technique. In chapter 3 we show the characteristics of the components we use to acquire these data, such as the T64000 spectrometer, in addition to the equipment for carrying out experiments under high pressures. In chapter 4 we will describe the main characteristics of Raman spectroscopy studies under high pressures for the material MHyMn(H2POO)3 where two structural phase transitions are observed in the interval between 1.0 atm and 7.9 GPa. Finally, in chapter 5 we show the main ones conclusions of the work.